Evaluating the Altarpiece: Image Decorum in Post-Tridentine Apostolic Visitations - Harpster, Grace (Religions, 2023)
This essay seeks to shift our perspective when addressing the question of the impact of the Council of Trent on art. Rather than focusing on the artistic treatises that emerged in the wake of the council, it turns to a different type of text: the records from visitations, regular church inspections that functioned as an important tool of Catholic reform. This analysis looks at apostolic visitation records in the Vatican archives between 1564 and 1630 to show how ecclesiastical visitors chiefly judged image decorum—and the definition of images themselves—according to function instead of form, giving priority to issues related to ritual use, such as conservation, consecration, and location. The functional definition of terms such as altarpiece and icona in the visitation records also reminds us to carefully consider the art historical vocabulary used in scholarship today.